Generating, evaluating, endorsing, and implementing malevolent creativity: a malevolent idea journey - Perchtold-Stefan, Corinna; Rietzschel, Eric; Baas, Matthijs (Frontiers in Psychology, 2025)
Over the last years, malevolent creativity research has delved into creative ideas that intend to harm both on the smaller and larger scale (from creative bullying or deception to terrorism and warfare) in different settings (personal revenge, organizational level, crime). Here, studies have almost exclusively focused on generating/having malevolently creative ideas, either by having people self-report frequency of such ideas, or by measuring their performance on malevolent creativity tests. However, according to stage-based creativity models, (malevolent) idea generation is only one, arguably less consequential aspect of the creative process. Indeed, having harmful creative ideas does not equate assigning them a high value, endorsing them in others, nor implementing them in real-life, which is what ultimately causes societal damage. In this paper, we first summarize the previous research insights on malevolent idea generation, including links to divergent thinking, personality, emotion, and environmental factors. We then offer novel perspectives and avenues for the future of malevolent creativity research by discussing stages beyond idea generation like idea evaluation and forecasting, as well as the endorsement, selection and implementation of harmful creative ideas. Supporting our theoretical arguments, we also include hitherto unpublished research findings from our labs as a basis for discussion. Overall, this paper is intended as a springboard to discuss ways for approximating the malevolent idea journey toward actual idea implementation in malevolent creativity research, i.e., how people transition from generating malevolent creative ideas to executing malevolent creativity actions in real-life (malevolent innovation).